Pemberdayaan Ekonomi Melalui Pendidikan Kewirausahaan di Dayah Nurul Huda Aceh Utara: Implementasi, Tantangan, dan Strategi Pengembangan - Rizka, Riza Nurul; Salabi, Agus Salim (Pascasarjana IAIN Lhokseumawe, 2025)
This study aims to analyse the model of economic empowerment through the entrepreneurship program at Dayah Nurul Huda, as well as to examine its challenges, supporting factors, and development strategies within the context of modern Islamic boarding school education. The research employed a qualitative descriptive approach with a case study design, using in-depth interviews, participatory observation, and document analysis. Data were analysed thematically to identify patterns of meaning emerging from entrepreneurial practices within the dayah. The findings reveal that the entrepreneurship program at Dayah Nurul Huda integrates Islamic values such as ikhtiar (effort), amanah (trustworthiness), and barakah (divine blessing) with modern management principles based on competence and collaboration. This model gives rise to the concept of “spirituality-based entrepreneurship”, which harmonizes economic orientation with the cultivation of religious character. The main challenges identified include limited financial resources, insufficient entrepreneurship training for teachers (ustaz), and traditional management practices. Meanwhile, significant support stems from collaboration among the dayah, local government, universities, and micro, small, and medium enterprises (MSMEs), which collectively expand business networks and strengthen institutional capacity. These findings are expected to serve as a reference for enhancing the economic self-reliance of Islamic boarding schools and for developing an Islamic entrepreneurship curriculum that remains relevant to contemporary challenges.